Development of Social and Civic Competence in the Classroom through Art - Romera, Catalina Guerrero; Prados, Maria Angeles Hernnndez; Vicent, Patricia Lopez; Henarejos, Ana Carmen Tolino Fernandez- (Asian Journal of Contemporary Education, 2020)
The competency-based model implies a process of humanization of education that diversifies content, focusing in this case on the development of the civic and artistic competence of the students. This paper presents the CIVABLES Program designed within the framework of teaching and research collaboration between the University and the Primary School. The program is structured around three pillars: the development of basic skills in the primary education curriculum, education in values and art as an educational resource that facilitates the overall development of students. The contents of the program have been defined by the selection of the work of Italo Calvino "The Invisible Cities", following the recommendations and experience of the team of teachers who teach in the school. The result has been the design of a totally innovative proposal within the educational field that can contribute not only to the development and conservation of cultural and artistic heritage, but also to address the basic skills through art and education in values to train citizenship.